The Foreign Economic Vector of Agribusiness Activity in the Western Region of Ukraine - Yuriy Hubeni; Oksana Krupa; Volodymyr Krupa; Sofiia Tsiolkovska (Zeszyty Naukowe Szkoły Głównej Gospodarstwa Wiejskiego w Warszawie. Problemy Rolnictwa Światowego)
The article is devoted to researching peculiarities and trends of foreign economic activity of agribusinesses in the Western region of Ukraine according to the terms of the Ukraine-European Union Association Agreement. The authors discuss the theoretical essence of agribusiness, as a kind of entrepreneurship, and the nature of foreign economic activity of enterprises. The main conditions of free trade in agricultural products introduced by the terms of the Agreement are determined and their influence on agribusiness export-import operation dynamics in the Western economic region is analyzed. The contribution of certain regions to forming agrarian product export and import volume and structure is considered and the reasons for the considerable advantages of the Lviv region in foreign trade turnover of the Western region are elucidated. It was found that agribusiness cooperation with foreign partners is mainly realized by indirect methods through trade agency organizations or agrarian holding companies. The structure dynamics of production goods for export and import by agribusinesses was studied. Based on the results, some negative tendencies for the Ukrainian economy were noted. They include the preservation of raw exports with a high share of plant origin products and timber, and the predominance of ready-made products with high added value in the import structure. It was established that the Agreement and social political events in Ukraine changed the direction of some export-import flows of agribusiness from CIS countries towards the markets of the European Union and Asian countries. According to the scale of external trade operations with enterprises of the Western region of Ukraine, in general, and within certain trade groups, in particular, country-leaders are defined. Some positive and negative consequences of changes in the foreign economic activity vector are described. And finally, measures which will ensure an expansion and strengthening of Ukraine’s agribusiness presence on international market, are suggested.